Forensic Nursing Science Knowledge and Competency. Issue 1 (January 2015) - Drake, Stacy A.; Langford, Rae; Young, Anne; Ayers, Constance
<x xml:space="preserve">Abstract</x> Forensic nursing is a nursing specialty that provides services to a variety of patient populations who have experienced violence, including interpersonal violence, sudden or unexpected death, and motor vehicle collisions. However, many critical care nurses have received the background knowledge or practical skills required to provide the level of care required by many forensic patients. The purpose of this study was to determine whether differences in knowledge or practical competence exist between participants using 2 different learning modalities: medium fidelity simulation versus face-to-face lecture. Participants who were enrolled in an elective online forensic nursing science course were randomly assigned to an intervention or control group. The 18 intervention group participants were given three 2-hour forensic simulation sessions in the laboratory. The 17 control group participants attended 3 face-to-face lectures covering forensic science topics. All study participants also received the same forensic course content via the online Blackboard platform. No significant differences were found between the 2 groups in either knowledge or practical competency. The lack of results may have been heavily influenced by the small sample size, which resulted in insufficient power to detect possible differences.